Intronic mutation of the VHL gene associated with central nervous system hemangioblastomas in two Chinese families with Von Hippel–Lindau disease: case report - Liu, Zhen (BMC Med Genet, 2020)
BACKGROUND: Central nervous system (CNS) hemangioblastomas are the most frequent cause of mortality in patients with Von Hippel–Lindau (VHL) disease, an autosomal dominant genetic disease resulting from germline mutations in the VHL tumor suppressor gene, with most mutations occurring in the exons. To date, there have been no reports of CNS hemangioblastoma cases related to pathogenic variants in intron 2 of VHL, which encodes a tumor suppressor protein (i.e., pVHL) that regulates hypoxia-inducible factor proteins. CASE PRESENTATION: We report the presence of a base substitution of c.464-1G > C and c.464-2A > G in the intron 2 of VHL causing CNS hemangioblastomas in six patients with VHL from two Chinese families. The clinical information about the two pathogentic variants has been submitted to ClinVar database. The ClinVar accession for NM_000551.3(VHL):c.464-1G > C was SCV001371687. This finding may provide a new approach for diagnosing and researching VHL-associated hemangioblastomas. CONCLUSIONS: This is the first report of a pathogenic variant at intron 2 in VHL-associated hemangioblastomas. Gene sequencing showed that not only exonic but also intronic mutations can lead to the development of CNS hemangioblastomas.